(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The contribution aims to investigate the specificity of freedom of expression concerning opinions or information in the field of abortion. After a theoretical introduction on the terms of the issue, a distinction is made between the different dimensions of this freedom, which range from the split between the active and passive dimension of the law (giving and receiving information on abortion services), to the enucleation of a positive and a negative one (wanting to be informed or refusing to receive information), up to the configuration of a duty of information. The essay then investigates the extent of freedom of expression and its limits with specific reference to some recent decisions regarding ideologically oriented manifestos. It concludes by noting the need for a constraint on the truthful content of public communications regarding abortion.